Produção animal e características da pastagem de Coastcross consorciada com Arachis pintoi, com e sem nitrogênio - Ribeiro, Ossival Lolato (2007)
The present study it objective to evaluate the effect of the intercropping between Coastcross-1 (Cynodon dactylon [ L ] Pers Cv Coastcross-1) and Arachis pintoi, in different levels of nitrogen fertilization, under grazing, on the animal productivity, production and chemical composition of forage, as well as the effect on the biomass and organic reserves of the forage root system of the pasture,using a following treatments: Coastcross + Arachis pintoi; Coastcross + Arachis pintoi with 100 kg.ha-1 of N; Coastcross + Arachis pintoi with 200 kg.ha-1 of N; and Coastcross with 200 kg.ha-1 of N, and the station of the year: winter, spring, summer and autumn. The desing used was a randomized block with two repetitions. The experiment was carried in the Experimental Station of the Agronomic Institute of the Paraná, in Paranavaí city, in the northwest of Paraná State, during the months of July/2005 through June/2006. The grazing method was to continuous stocking and variable stocking rate, and the animals used were crossbred heifers (Zebu x Eropean), using three testers with an average weight of 170 kg, with forage offers of 6,63% of PV and forage availability of 1.604 kg of MS. The Coastcross + Arachis pintoi with 200 kg.ha-1 of N use as well as the best climatic conditions during the Spring and Summer gotten the favorable to forage mass (26.764 kg.ha-1) and to forage mass dairy accumulation (82 kg.ha-1 of MS). The use of Arachis pintoi with 200 kg.ha-1 of N and Coastcross with kg.ha-1 of N had been determinative for the best animal performance in Coastcross pasture (P <0,05), providing a GMD of 0,570 and 0,500, a GPV of 2.151 and 1.717 kg.ha-1, and stocking rate of 3,51 and 3,26 UA.ha-1, respectively. With relation to the composition of forage, the used nitrogen fertilization, especially in raised amounts, provides to the biggest percentages of green leaf blade and leaf sheath + green stem, however, with reduction in the percentages of dead material and Arachis pintoi. The nitrogen fertilization associate to the Arachis pintoi improved the nutritional values of the Coastcross, that presented average texts of 17 % of PB, 67 % of FDN and 73 % of DIVMS. The used of nitrogen fertilization (100 kg.ha-1) associated to the Arachis pintoi provided to greater concentration of non-structural carbohydrate (0,3942 g.ha-1) and a greater root biomass (0,4483 kg.m-3). The concentration of carbohydrate and the root biomass had been raised in the Summer and Autumn. The concentration of root biomass was 63%, 24% and 13% in the depths of 0 - 15, 15 - 30 and 30 - 45 cm, however, did not have difference in the root biomass between the treatments, in the studied depths. The carbohydrate concentrations had been similar in the different depths of the roots. When the nitrogen fertilization is used, associate to the Arachis pintoi, in thestations of the year where the climatic conditions had been favorable, it had a better growth of the grass and greater forage production, improving the nutritional value of the pasture and the animal performance.